Grhl3 promotes retention of epidermal cells under endocytic stress to maintain epidermal architecture in zebrafish. - Mandar Phatak; Shruti Kulkarni; Lee B Miles; Nazma Anjum; Sebastian Dworkin; Mahendra Sonawane (PLoS Genetics, 2021)
Epithelia such as epidermis cover large surfaces and are crucial for survival. Maintenance of tissue homeostasis by balancing cell proliferation, cell size, and cell extrusion ensures epidermal integrity. Although the mechanisms of cell extrusion are better understood, how epithelial cells that round up under developmental or perturbed genetic conditions are reintegrated in the epithelium to maintain homeostasis remains unclear. Here, we performed live imaging in zebrafish embryos to show that epidermal cells that round up due to membrane homeostasis defects in the absence of goosepimples/myosinVb (myoVb) function, are reintegrated into the epithelium. Transcriptome analysis and genetic interaction studies suggest that the transcription factor Grainyhead-like 3 (Grhl3) induces the retention of rounded cells by regulating E-cadherin levels. Moreover, Grhl3 facilitates the survival of MyoVb deficient embryos by regulating cell adhesion, cell retention, and epidermal architecture. Our analyses have unraveled a mechanism of retention of rounded cells and its importance in epithelial homeostasis.